Comparative analysis of cognitive behavioral therapy and dialectical behavior therapy in enhancing psychological capital among medical students: a randomized controlled trial - Dong, Cexin; Zhao, Jinfa; Wei, Yating; Wu, Deyuan; Cai, Zhu (Frontiers in Psychology, 2024)
Background: Medical students are confronted with a complex stress environment, encompassing academic challenges, residency training, and future workplace pressures. Therefore, the exploration of effective psychological capital intervention strategies is crucial for enhancing their mental health and promoting career development. Objective: The aim of this study was to evaluate the efficacy of group cognitive-behavioral therapy (GCBT) and dialectical behavior therapy (DBT) in boosting the psychological capital of medical students and to compare the advantages and disadvantages of these two therapies. Method: A randomized controlled trial was conducted, recruiting 56 second-year medical students, who were randomly assigned into three groups: GCBT intervention group, DBT intervention group, and control group. The intervention period lasted for 6 weeks, during which the GCBT and DBT groups received respective interventions, while the control group did not receive any intervention.Results: Regardless of whether GCBT or DBT was used as an intervention, the psychological capital levels of the intervention group students showed significant improvement (mean ± SD, P<0.05), with effect sizes ranging from 0.324 to 0.667. Further follow-up studies revealed that this improvement remained stable within one month post-intervention (mean ± SD, P<0.05). Conclusion: Both group cognitive-behavioral therapy (GCBT) and dialectical behavior therapy (DBT) have been proven to be effective psychological intervention methods, capable of significantly enhancing the psychological capital of medical students. However, there are certain differences in their effects, providing diverse intervention options to cater to the varied psychological needs of medical students.